Analisis Efektivitas Penggunaan E-Filing pada Wajib Pajak Orang Pribadi di Kantor Pelayanan Pajak Pratama Bekasi Barat - Thasya Josephin; Adam Zakaria; Dwi Handarini (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study aims to analyze the effectiveness of e-Filing in reporting Annual Tax Returns by Individual Taxpayers (WPOP) at the West Bekasi Pratama Tax Office (KPP Pratama). The background of this study stems from the challenges in improving taxpayer compliance, despite the implementation of an electronic reporting system (E-Filing) by the Directorate General of Taxes. The research method used is a descriptive qualitative approach with a case study technique. Data were obtained through interviews, documentation, and literature review. Data analysis was carried out using data reduction, data presentation, and conclusion drawing techniques. The results show that the use of e-Filing is quite effective, with the effectiveness ratio of Annual Tax Return reporting by Individual Taxpayers ranging from 85% to 88% during the 2021–2023 period. However, the level of taxpayer compliance has actually decreased from year to year, indicating that the system's effectiveness has not fully impacted compliance improvements. WPOP's perception of e-Filing is generally positive, especially in terms of ease and flexibility of use. However, there are still technical barriers and limited understanding in its use. From the perspective of tax officials, obstacles encountered include a lack of education, a surge in users around deadlines, and limited infrastructure. This study concludes that while e-Filing has helped improve reporting efficiency and taxpayer satisfaction, its success in increasing compliance still depends on other external factors such as education, outreach, and mentoring. Recommendations include improving the quality of digital services, more intensive public education, and developing a more user-friendly system.